The antimicrobial sensitivity of Streptococcus mutans and Streptococcus sangius to colloidal solutions of different nanoparticles applied as mouthwashes - Ahrari, Farzaneh (Dent Res J (Isfahan), 2015)
BACKGROUND: Metal nanoparticles have been recently applied in dentistry because of their antibacterial properties. This study aimed to evaluate antibacterial effects of colloidal solutions containing zinc oxide (ZnO), copper oxide (CuO), titanium dioxide (TiO(2)) and silver (Ag) nanoparticles on Streptococcus mutans and Streptococcus sangius and compare the results with those of chlorhexidine and sodium fluoride mouthrinses. MATERIALS AND METHODS: After adding nanoparticles to a water-based solution, six groups were prepared. Groups I to IV included colloidal solutions containing nanoZnO, nanoCuO, nanoTiO(2) and nanoAg, respectively. Groups V and VI consisted of 2.0% sodium fluoride and 0.2% chlorhexidine mouthwashes, respectively as controls. We used serial dilution method to find minimum inhibitory concentrations (MICs) and with subcultures obtained minimum bactericidal concentrations (MBCs) of the solutions against S. mutans and S. sangius. The data were analyzed by analysis of variance and Duncan test and P < 0.05 was considered as significant. RESULTS: The sodium fluoride mouthrinse did not show any antibacterial effect. The nanoTiO(2)-containing solution had the lowest MIC against both microorganisms and also displayed the lowest MBC against S. mutans (P < 0.05). The colloidal solutions containing nanoTiO(2) and nanoZnO showed the lowest MBC against S. sangius (P < 0.05). On the other hand, chlorhexidine showed the highest MIC and MBC against both streptococci (P < 0.05). CONCLUSION: The nanoTiO(2)-containing mouthwash proved to be an effective antimicrobial agent and thus it can be considered as an alternative to chlorhexidine or sodium fluoride mouthrinses in the oral cavity provided the lack of cytotoxic and genotoxic effects on biologic tissues.